Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Pengelolaan Keuangan Pribadi Mahasiswa Fakultas Hukum Universitas Andi Djemma Palopo - Munawir Munawir; Muh. Haekal Yunus; Fransiska Asriani Samma; Eliyana Eliyana; Amanda Putri (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
This study aims to determine the influence of financial literacy and lifestyle on personal financial management of students at the Faculty of Law, Andi Djemma Palopo University. The population of this study was all students at the Faculty of Law, Andi Djemma Palopo University, and a sample of 50 respondents was used. This study used a quantitative research method by distributing questionnaires to respondents. The results of the multiple linear regression analysis (MLA) in this study indicate that simultaneously, financial literacy and lifestyle have a significant and positive effect on personal financial management. Partially, financial literacy and lifestyle have a significant and positive effect on personal financial management. These results further support the assertion that the better an individual's financial literacy and lifestyle, the better their financial management.